Analog quantum simulation of the Rabi model in the ultra-strong coupling regime - Jochen Braumüller (Nature Portfolio, 2017)
An analog quantum simulation scheme has been explored with a quantum hardware based on a superconducting circuit. Here the authors investigate the time evolution of the quantum Rabi model at ultra-strong coupling conditions, which is synthesized by slowing down the system dynamics in an effective frame.